Quercetin Stabilizes Atherosclerotic Plaques by Reducing Matrix Metalloproteinase-9 Expression and Enhancing M2 Macrophage Activity in Wistar Rats - Romi Ermawan; Budi Susetyo Pikir; Mulyanto Mulyanto; Budi Utomo; Widjiati Widjiati; Yudi Her Oktaviono (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Quercetin has been shown to alleviate and prevent atherosclerosis. However, its role in stabilizing atherosclerotic plaques to prevent plaque rupture remains unclear. Therefore, this study was conducted to investigate the effects of quercetin on stabilizing atherosclerotic plaques.METHODS: Thirty-two Wistar rats were objected to a high-fat diet, along with an endothelial injury procedure conducted during the second week to create atherosclerotic plaque models. After six weeks, the subjects were randomly assigned to five groups consist of two control groups and three treatment groups treated with different quercetin dosages. Following the treatment, all subjects were euthanized to collect the left common carotid artery. The stability of the atherosclerotic plaques was evaluated by measuring the expression of matrix metalloproteinase-9 (MMP-9) using real-time polymerase chain reaction, assessing the activity of M1 and M2 macrophages along with the M1/M2 ratio using an enzyme-linked immunosorbent assay, and determining the maximum intima thickness through histopathological examination.RESULTS: Quercetin significantly reduced the expression of MMP-9, increased the activity of M2 macrophages, and lowered the M1/M2 ratio at doses of 10 and 50 mg/kg. However, there was no effect on M1 macrophage activity or maximum intima thickness. Path analysis indicated that quercetin primarily enhanced atherosclerotic plaque stability by reducing MMP-9 expression (p<0.001) and subsequently enhancing M2 macrophage activity (p=0.002).CONCLUSION: Quercetin administration significantly decreased the expression of MMP-9, enhanced the activity of M2 macrophages, and lowered the M1/M2 ratio at specific doses. These findings emphasize the significance of quercetin in stabilizing atherosclerotic plaques.KEYWORDS: atherosclerotic plaque, quercetin, stability, Wistar rats